Responses and roles of roots, microbes, and degrading genes in rhizosphere during phytoremediation of petroleum hydrocarbons contaminated soil. Issue 12 (15th October 2019) - Cheng, Lijuan; Zhou, Qixing; Yu, Binbin
Abstract: Rhizodegradation performed by plant roots and the associated bacteria is one of the major mechanisms that contribute to removal of petroleum hydrocarbons (PHCs) during phytoremediation. In this study, the pot-culture experiment using wild ornamental Hylotelephium spectabile (Boreau) H. Ohba was designed to explore responses and roles of roots, microbes, and degrading genes in the rhizodegradation process. Results showed that PHCs degradation rate by phytoremediation was up to 37.6–53.3% while phytoaccumulation accounted for a low proportion, just at 0.3–13.3%. A total of 37 phyla were classified through the high throughput sequencing, among which Proteobacteria, Actinobacteria, and Acidobacteria were the three most dominant phyla, accounting for >60% of the phylum frequency. The selective enrichment of PHC degraders with high salt-tolerance, including Alcanivorax and Bacteroidetes, was induced. Generally, relative abundance of the PHC degrading genes increased significantly with an increase in PHCs concentrations, and the gene copy number in the phytoremediation group was 1.46–14.44 times as much as that in the unplanted controls. Overall, the presence of PHCs and plant roots showed a stimulating effect on the development of specific degraders containing PHC degrading genes, and correspondingly, a biodegradation-beneficial community structure had been constructed to contribute to PHCs degradation in the rhizosphere.